As relações de trabalho no contexto da crise do capital no Brasil: a reforma trabalhista do governo Temer - PINHEIRO, Stefanny Monteiro (2021)
ABSTRACT This work analyzes the changes in labor relations in the context of the capital crisis in Brazil in the light of the labor reform sanctioned by Michel Temer's government. The hypothesis is that the reform deepens the precariousness of labor relations in Brazil and brings a tendency to transform workers into a relative overpopulation, causing the regression of social and labor rights. The Consolidation of Labor Laws - CLT completed 74 years on May 1, 2017. During this period, it underwent several reforms, not all of equal scope. Law 13,467 / 2017, which came into force on 11/11/2017, has been criticized by many authors who emphasize the damage to workers and the government's shady objectives, which spared no effort to pass it. Accusing the CLT of being outdated, the reform advocates raised their flag without fully discussing its effects. To confirm the hypothesis, a bibliographic research was carried out based on a specialized literature for the appropriation of the main guiding categories of the study and for the discussion of changes in labor relations from the capital crisis and the process of productive restructuring in the world and specifically in Brazil; and documentary analysis of data from IBGE, DIEESE, PNAD, CAGED etc. After carrying out this work, it is possible to conclude that the labor reform represents yet another effort to defend the unilateral interests of the plundering of workers with the deregulation of social and labor rights previously conquered.